Pengaruh Media Edukasi BOGIMBA (Boneka dan Dongeng Gizi Seimbang) terhadap Tingkat Pengetahuan Anak tentang Gizi di TK Islam Silmi Samarinda - Ainur Basirah Mulya; Meiliati Aminyoto; Nurul Hasanah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
The main causes of the nutritional problems is poor diet. Knowledge became one of the aspects that affect it. Therefore, it is extremely important nutrition education given at an early age. This study aims to determine the effect of educational media BOGIMBA (Doll and Tale of Balanced Nutrition) to the level of knowledge of children about nutrition to the type of analytical research quasi-experimental method is based on the design of one group pretest-posttest. This research sample using the entire sample of the population that met the inclusion criteria of research to obtain 51 respondents. The variables measured in this study are BOGIMBA educational media and level of knowledge of children about nutrition. From the research conducted, it was found the influence of educational media BOGIMBA to increase children's knowledge about nutrition (p = 0.000).